The killing of George Floyd - Harris, Duchess; Burling, Alexis (Special reports., 2021)
Discusses the shooting of George Floyd by Minneapolis police, and explores the history of police brutality in the United States. Examines the national and global response to his death. Includes color photographs, sidebars, a timeline, a glossary, and additional resources.